Pengaruh Dana Desa Dan Infrastruktur Terhadap Ketimpangan Pendapatan Perdesaan Antar Provinsi Di Sumatera Bagian Selatan - Hutapia; Izharudin, Izharudin; Benardin, Benardin (Jurnal AGRISEP, 2023)
The purpose of this study was to determine the effect of village funds and infrastructure on income inequality between provincial governments in Southern Sumatera. This study uses a panel data regression model, the data used are secondary data from 2015 to 2020. The data used in this study are time series data obtained from Badan Pusat Statistik (BPS), Ministry of Finance, Ministry of Public Works and Housing People (PUPR) and other related agencies. Based on research and data processing, the best panel data regression model is the fixed effect model. The results of the F-statistical test show that the variables of village funds, road infrastructure, electricity ratios, and cellular telephone ownership jointly reduce income inequality between villages between provincial governments in Southern Sumatera significantly. Meanwhile, based on the statistical results of the t-test, only household cell phone ownership has no significant effect on rural income inequality.